Interleukin-6 bedside testing in women at high risk of preterm birth. (16th November 2010) - Vousden, N; Chandiramani, M; Shennan, AH
Abstract : Objective: Infection is likely to contribute to the complex aetiology of preterm birth (PTB). It can be detected using white blood cell count and C-reactive protein (CRP). However, nearly 10% of women have subclinical infection. Laboratory analysis has demonstrated that vaginal interleukin-6 (IL-6) is correlated with PTB. The authors aimed to investigate a bedside test in this context. Method: Vaginal secretions were collected from women at high risk of PTB. Samples were incubated for 20 min then analysed by the bedside optical reader (IL-6 in pg/ml). Maternal and neonatal infectious markers and pregnancy outcome were recorded. Results: In the 80 women investigated, IL-6 was able to predict PTB, latency to gestation and maternal infection with some efficacy. It was a poor predictor of neonatal infection. Women with visible fetal membranes had significantly higher IL-6 concentrations than those with closed cervices (p=0.002). All of those with visible membranes and a high IL-6 (>50 pg/ml) had a PTB (n=12) compared to half of those with a low IL-6 (<50 pg/ml, n=1). No women with a low IL-6 delivered at <24 weeks' compared to 83% (n=10) of those with high IL-6. In women with prelabour premature rupture of membranes (PPROM), high IL-6 was associated with more extreme PTB's (57% vs 0%, p=0.19) and delivery within 7 days (71% vs 50%, p=0.09). Conclusion: IL-6 may be useful in guiding the difficult management of patients with visible membranes and PPROM, for example the potential benefit of a cervical cerclage and antibiotics.